A life-cycle model with ambiguous survival beliefs - Max Groneck; Alexander Ludwig; Alexander Zimper (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Based on a cognitive notion of neo-additive capacities reflecting likelihood insensitivity with respect to survival chances, we construct a Choquet Bayesian learning model over the life-cycle that generates a motivational notion of neo-additive survival beliefs expressing ambiguity attitudes. We embed these neo-additive survival beliefs as decision weights in a Choquet expected utility life-cycle consumption model and calibrate it with data on subjective survival beliefs from the Health and Retirement Study. Our quantitative analysis shows that agents with calibrated neo-additive survival beliefs (i) save less than originally planned, (ii) exhibit undersaving at younger ages, and (iii) hold larger amounts of assets in old age than their rational expectations counterparts who correctly assess their survival chances. Our neo-additive life-cycle model can therefore simultaneously accommodate three important empirical findings on household saving behavior.
Keywords: D91; D83; E21; 330; Bayesian learning; likelihood insensitivity; ambiguity; Choquet expected utility; dynamic inconsistency; life-cycle hypothesis; saving puzzles